PENGARUH CITA RASA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA RESTORAN YUMMY FOODCOURT MEDAN (KOMPLEK CEMARA ASRI) - Astifa Bawamenewi; Aswand Hasoloan (LPPM Universitas HKBP Nommensen, 2022)
The business of today is booming into a culinary business. The proliferation of culinary enterprises in a similar way causes competition to become more intense. Thus, in the face of such circumstances and circumstances, the company must be capable and aware and swift in making decisions for the established businesses to thrive and should also be able to maintain the market and win the competition. The study was intended to know the quality of taste, and the quality of service to the customer's satisfaction at the yummy food court court restaurant. Customer satisfaction is the main thing to be accomplished in service. This is because when the quality of service rendered does not satisfy the customer, it does not preclude the possibility of the customer being unfaithful to the restaurant. So under these conditions the company is required to measure customer satisfaction in order to establish anything short of a service that makes the customer dissatisfied. This type of research USES a quantitative method with technical sampling of this research is sampling sampling. The source of this research is the primary data derived from the sample of the consumer who visits the yummy food court field restaurant. Data collection is done by disseminating a questionnaire to 100 respondents. Technical data analysis used for verification and containment tests, the classic assumption test of normality (histogram, p-plot, colmogorov snov), multicollagality test and heteroskelity test, the regression test, double tests and hypothetical tests. Based on studies and discussions it can be concluded that the variables of taste and quality of service affect positive and significant customer satisfaction in the yummy food court court restaurant.